2015
DOI: 10.1007/s00424-015-1764-7
|View full text |Cite
|
Sign up to set email alerts
|

TRPM4-dependent post-synaptic depolarization is essential for the induction of NMDA receptor-dependent LTP in CA1 hippocampal neurons

Abstract: TRPM4 is a calcium-activated but calcium-impermeable non-selective cation (CAN) channel. Previous studies have shown that TRPM4 is an important regulator of Ca2+-dependent changes in membrane potential in excitable and non-excitable cell types. However, its physiological significance in neurons of the central nervous system remained unclear. Here, we report that TRPM4 proteins form a CAN channel in CA1 neurons of the hippocampus and we show that TRPM4 is an essential co-activator of N-methyl-d-aspartate (NMDA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 40 publications
4
46
0
Order By: Relevance
“…Acceleration was correlated with the TRPM4 current and modeling predicted that the TRPM4 channels, coupled to Calmodulin through intracellular Ca 2+ changes, could effectively generate firing acceleration about 1.5 seconds after the beginning of discharge, i.e. when acceleration was observed experimentally (Shin et al, 2008;Shin et al, 2009;Kim et al, 2013;Menigoz et al, 2016). This delay reflected the slow cooperative gating of TRPM4 channels, that opened only after the Ca 2+ -Calmodulin complex reached a threshold.…”
Section: Parameter Tuning As the Basis Of Granule Cell Subtype Differmentioning
confidence: 97%
See 2 more Smart Citations
“…Acceleration was correlated with the TRPM4 current and modeling predicted that the TRPM4 channels, coupled to Calmodulin through intracellular Ca 2+ changes, could effectively generate firing acceleration about 1.5 seconds after the beginning of discharge, i.e. when acceleration was observed experimentally (Shin et al, 2008;Shin et al, 2009;Kim et al, 2013;Menigoz et al, 2016). This delay reflected the slow cooperative gating of TRPM4 channels, that opened only after the Ca 2+ -Calmodulin complex reached a threshold.…”
Section: Parameter Tuning As the Basis Of Granule Cell Subtype Differmentioning
confidence: 97%
“…The depolarization-induced slow current (DISC) is a depolarizing current gated by the raise of intracellular Ca 2+ that follows action potential bursts and NMDA channel activation, and can typically generate a secondary burst after 1.5-2 secs like that observed in accelerating GrCs (Shin et al, 2008;Shin et al, 2009;Menigoz et al, 2016). DISC is typically generated by TRPM4 (Kim et al, 2013), a Ca 2+ -activated non-selective cation channel which provides a strong depolarizing drive upon Ca 2+ entry (Petersen, 2002).…”
Section: Trp Current Expression In Accelerating Grcsmentioning
confidence: 99%
See 1 more Smart Citation
“…TRPM4 expression in substantia nigra pars compacta may play an important role in the plateau potential and burst firing of dopaminergic neurons ( Mrejeru et al, 2011 ). Additionally, TRPM4 participates in the dendritic depolarization necessary to induce certain forms of LTP in the hippocampal CA1 area ( Menigoz et al, 2016 ). Recently, Lei et al (2014) demonstrated that TRPM4 is expressed in pyramidal neurons of layer 5 in mouse mPFC.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the transient receptor potential (TRP) channel family, a family of nonselective cation channels, have been shown to modify synaptic plasticity in various brain regions including the hippocampus (Gibson et al 2008;Li et al 2008;Chávez et al 2010;Menigoz et al 2016), entorhinal cortex (Banke 2016), nucleus accumbens (Grueter et al 2010), and superior colliculus (Maione et al 2009). In the LA, we have previously demonstrated that LTP is attenuated by capsaicin via activation of TRPV1 (Zschenderlein et al 2011) whereas LTD is enhanced by capsaicin via activation of TRPM1 (Gebhardt et al 2016).…”
mentioning
confidence: 99%